A rare location of primary extrahepatic hydatid cyst in the soft tissue - Shanker, S. Uma; Sreenivas, U. V. Sai; Swathanthra, N. (International Surgery Journal, 2020)
Hydatid cyst or cystic echinococcosis in human is rare disease caused by tapeworm Echinococcus granulosa. Hydatid cyst of soft tissue is a rare condition and we had a case of large hydatid cyst in lumbar region. This is a case of 48 years old female presented to us during October 2018 with a large diffuse swelling over the left lumbar region which was gradually grown over the last 2 years without pain. The diagnosis of hydatid cyst was not sure even in CT scan but it was in our differential diagnosis. It is confirmed during surgery after seen the multiple cyst removed from the large cystic lesion. No recurrence even after 15 months of follow up. Presence of hydatid cyst in soft tissue is usually rare and its diagnosis is not expected clinically when it presents as a soft tissue swelling. We need to confirm it during surgery or by presence of typical germinal membrane under microscope.